“These forces are in our midst”: YWCA “Girls” and Challenges of Transnationalism Between the Wars - Warne, Ellen (Australasian Journal of Victorian Studies, 2013)
This article considers the effectiveness of transnational ties in the YWCA between the wars. The Association had established their network of women and “girls” long before World War One and were able to resume their connections after the war when the League of Nations raised the possibility of new ways of tackling social inequalities. They hoped that their “girl” members would become “world citizens”: a status that would both offer a stimulating and greater role to adolescent workers performing industrial work, as well as a way of promoting girls’ leadership and contributions to an evolving world. This article explores the tension that transnationalism presented the Association in this period as polarised political forces increasingly made work on “industrial problems”—even for “girls”—apparently suspect.